ANALISIS PENGARUH KUALITAS JASA TERHADAP KEPUASAN DAN INTENSI PERILAKU PELANGGAN DALAM PELAYANAN AIR BERSIH - Suliantoro, Hery; Ririh, Kirana Rukmayuninda (J@ti Undip : Jurnal Teknik Industri, 2013)
Nowadays, most of PDAM (Public Drinking Water Services) suffers from bankruptcy, because PDAMs have to pay their loan from an International Funding.  There is more than 300 PDAMs in Indonesia trap in financial problem that have to pay credits approximately Rp 5,3 Billion.  The main aim of the loan was to rise service level of public service in PDAM, but in fact it turns to be a `boomerang` for PDAM itself in financial and operational fields.  Therefore, PDAM could not maximize its public service in expanding pipes to cover public needs of drinking water and advancing water quality.  In other side, the number of citizen who need water keeps arise year by year.  Today, PDAM Kabupaten Semarang Cabang Ungaran  onlycan cover public needs of clear water for about 68%.  The less service level in public service cause consuming level in public decreases.  The worst would be declining of company income in PDAM Kabupaten Semarang Cabang Ungaran.  For improving service quality, structural equation modelling is one of methods and way to identify factors and varibles that need to be improved rapidly.  This model was wellknown as a device to evaluate correlation every varible that has significancy to customer satisfaction in PDAM Kabupaten Semarang Cabang Ungaran.  For further,recommendation of improvement could be found in  this model evaluation.  Output of the structural equation modelling shows Reliability, Responsiveness, Assurance, and Emphaty dimensions have a positif correlation and significant to overall satisfaction but tangible dimension has no significant correlatiion.  Evaluation of overall satisfaction variable to behavvioural intention shows that overall satisfaction has a positive and significant correlation to word-of-mouth and behavioural intention.  Besides, overall satisfaction also has negative and no significant correlation to feedback Keywords : structural equation modelling, service quality dimension, overall satisfaction, behavioural intention